MANAJEMEN SARANA DAN PRASARANA DI MTsN BARITO SELATAN - ISNANIAH ISNANIAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The existing facilities and infrastructure in schools greatly determine the quality of the school and the learning process carried out will be helped if the school has complete facilities. Management of facilities and infrastructure is very important because with the management of facilities and infrastructure educational institutions will be maintained and clear their use. This study examines how to manage existing facilities and infrastructure in schools. The purpose of this study was to determine the utilization and maintenance of educational facilities. This research approach is qualitative with descriptive approach. Sources of data in this study were principals, managers of facilities and infrastructure, teachers and students. Data collection techniques through observation. The results of research and discussion can be concluded that school facilities and infrastructure greatly affect student learning outcomes, if the facilities and infrastructure in the school are complete, then learning will run optimally. Educational facilities include classrooms, learning media, tables, chairs and others. Meanwhile, infrastructure is a facility that indirectly functions to support learning activities such as yards, roads in schools. The existence of these school facilities and infrastructure as a tool to support the success of the process carried out by the school as an effort to provide services to the public, because without suggestions and infrastructure in schools, the teaching and learning process of teachers and students cannot run well and the expected results will not be achieved. . The existing facilities and infrastructure at MTsN Barito Selatan came from assistance from the government which was channeled through the Ministry of Religion, from community assistance and BAZNAS. ABSTRAKSarana dan prasarana yang ada di sekolah sangat menentukan kualitas sekolah dan proses pembelajaran yang dilaksanakan akan terbantu apabila sekolah memiliki fasilitas yang lengkap. Pengelolaan sarana dan prasarana sangat penting karena dengan adanya pengelolaan sarana dan prasarana lembaga pendidikan akan terpelihara dan jelas kegunaanya. Penelitian ini mengkaji tentang bagaimana memanajemen sarana dan prasarana yang ada di sekolah. Tujuan penelitian ini untuk mengetahui pemanfaatan dan pemeliharaan sarana pendidikan. Pendekatan penelitian ini adalah kualitatif dengan jenis pendekatan deskriptif. Sumber data dalam penelitian ini adalah kepala sekolah, pengelola sarana dan prasarana, guru dan peserta didik. Teknik pengumpulan data melalui observasi Hasil penelitian dan pembahasan dapat disimpulkan bahwa Sarana dan prasarana sekolah sangat berpengaruh terhadap hasil belajar peserta didik , apabila sarana dan prasarana yang ada di sekolah lengkap, maka pembelajaran akan berjalan optimal. Sarana pendidikan antara lain seperti ruang kelas, media pembelajaran, meja, kursi dan lain-lain. Sedangkan prasarana merupakan fasilitas yang secara tidak langsung berfungsi untuk menunjang kegiatan pembelajaran seperti halaman, jalan di sekolah. Keberadaan sarana dan prasarana sekolah ini sebagai alat untuk menunjang keberhasilan proses yang dilakukan sekolah sebagai upaya melakukan pelayanan terhadap public, karena tanpa adanya saran dan prasaran di sekolah maka proses belajar mengajar guru dan peserta didik tidak dapat berjalan dengan baik dan hasil yang diharapkan tidak akan tercapai. Sarana dan prasaran yang ada di MTsN Barito Selatan berasal dari bantuan dari pemerintah yang disalurkan melalui Departemen Agama, dari bantuan masyarakat dan BAZNAS.